GES-18, a New Carbapenem-Hydrolyzing GES-Type β-Lactamase from Pseudomonas aeruginosa That Contains Ile80 and Ser170 Residues - Bebrone, Carine (American Society for Microbiology, 2013)
A clinical isolate of Pseudomonas aeruginosa recovered from the lower respiratory tract of an 81-year-old patient hospitalized in Belgium was sent to the national reference center to determine its resistance mechanism. PCR sequencing identified a new GES variant, GES-18, which differs from the carbapenem-hydrolyzing enzyme GES-5 by a single amino acid substitution (Val80Ile, in the numbering according to Ambler) and from GES-1 by two substitutions (Val80Ile and Gly170Ser). Detailed kinetic characterization showed that GES-18 and GES-5 hydrolyze imipenem and cefoxitin with similar kinetic parameters and that GES-18 was less susceptible than GES-1 to classical β-lactamase inhibitors such as clavulanate and tazobactam. The overall structure of GES-18 is similar to the solved structures of GES-1 and GES-2, the Val80Ile and Gly170Ser substitutions causing only subtle local rearrangements. Notably, the hydrolytic water molecule and the Glu166 residue were slightly displaced compared to their counterparts in GES-1. Our kinetic and crystallographic data for GES-18 highlight the pivotal role of the Gly170Ser substitution which distinguishes GES-5 and GES-18 from GES-1.